Autobiography of Andrew Carnegie. - Carnegie, Andrew (Floating Press, 1920)
The industrialist, businessman, and philanthropist Andrew Carnegie (1835 - 1919) established a gospel of wealth that can be neither ignored nor forgotten, and set a pace in distribution that succeeding millionaires have followed as a precedent. In the course of his career he became a nation-builder, a leader in thought, a writer, a speaker, the friend of workmen, schoolmen, and statesmen, the associate of both the lowly and the lofty. But these were merely interesting happenings in ...